2021
DOI: 10.1007/s13258-021-01050-x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced fertility caused by meiotic defects and micronuclei formation during microsporogenesis in xBrassicoraphanus

Abstract: Background Hybridization and polyploidization events are important driving forces in plant evolution. Allopolyploids formed between different species can be naturally or artificially created but often suffer from genetic instability and infertility in successive generations. xBrassicoraphanus is an intergeneric allopolyploid obtained from a cross between Brassica rapa and Raphanus sativus, providing a useful resource for genetic and genomic study in hybrid species. Obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…We previously reported that some genomic regions of Br and Rs share structural similarity, particularly between A8 and R8, although most other regions are fragmented and diversified (Park et al ., 2020). In addition, we recently showed that several x B lines derived from the same intergeneric cross endured chromosome instability and pollen inviability, while occasionally producing tetrads with an extra micronucleus during microsporogenesis (Shin et al ., 2021). This is probably a consequence of homoeologous chromosome exchanges at meiotic prophase I leading to the formation of univalent or multivalent chromosomes (Shin et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that some genomic regions of Br and Rs share structural similarity, particularly between A8 and R8, although most other regions are fragmented and diversified (Park et al ., 2020). In addition, we recently showed that several x B lines derived from the same intergeneric cross endured chromosome instability and pollen inviability, while occasionally producing tetrads with an extra micronucleus during microsporogenesis (Shin et al ., 2021). This is probably a consequence of homoeologous chromosome exchanges at meiotic prophase I leading to the formation of univalent or multivalent chromosomes (Shin et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we recently showed that several x B lines derived from the same intergeneric cross endured chromosome instability and pollen inviability, while occasionally producing tetrads with an extra micronucleus during microsporogenesis (Shin et al ., 2021). This is probably a consequence of homoeologous chromosome exchanges at meiotic prophase I leading to the formation of univalent or multivalent chromosomes (Shin et al ., 2021). This suggests that chromosome instability persists in successive generations while generating nonfunctional haploid gametes with aberrant karyotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meiotic irregularities have been related to the origin of aneuploid gametes (Mursalimov and Deineko 2018), which impose detrimental effects on pollen development (Shin et al 2021). Out-of-plate and out-of-nucleus chromosomes can be caused by unequal tension from the poles (Lampson and Grishchuk 2017).…”
Section: Chromosome Behaviormentioning
confidence: 99%
“…Plants with male sterility cannot produce fertile pollen, and this male sterility may be regulated by genes encoded in the nuclear (genic male sterility) or mitochondrial (cytoplasmic male sterility) genomes ( Garcia et al., 2019 ). Abnormalities in the formation of the pollen sac ( Chaban et al., 2020 ; Zheng et al., 2021 ), meiosis ( Qiu et al., 2018 ; Shin et al., 2021 ), callose ( Pu et al., 2019 ; Li et al., 2020 ), tapetum ( Mondol et al., 2020 ; Zhang et al., 2021 ), pollen wall ( Ren et al., 2020 ; Deng et al., 2022 ), and anther dehiscence ( Kim and Kim, 2021 ; Qi et al., 2022 ) during pollen development can lead to pollen abortion and a male-sterile phenotype. Tapetum and meiocytes are primarily affected in most sporophytic male-sterile mutants ( Guo and Liu, 2012 ).…”
Section: Introductionmentioning
confidence: 99%